THE PRESIDENT OF THE REPUBLIC OF UZBEKISTAN AND THEIR SIGNIFICANT CONTRIBUTION TO THE DEVELOPMENT OF THE REPUBLIC OF UZBEKISTAN - Teshaboyeva Nafisa Zubaydulla qizi; Igor Chekulay Vladimirovich; G’oyibnazarova Oygul Olloqul qizi (Ta’lim innovatsiyasi va integratsiyasi, 2025)
Annotation:this article discusses the Presidents of the Republic of Uzbekistan and their significant contributions to the development of the country. It explains how each leader introduced important political, economic, and social reforms to strengthen independence, improve living standards, and modernize national institutions. The article highlights the achievements of the First President, Islam Karimov, who ensured stability during the early years of independence, created the Constitution, and established strong statehood. It also emphasizes the extensive reforms carried out by President Shavkat Mirziyoyev, who opened the country to the world, expanded international cooperation, and launched wide-ranging modernization programs.The article additionally outlines progress in key areas such as education, healthcare, economy, and cultural life under the leadership of Uzbekistan’s presidents. It describes efforts to preserve historical heritage, support youth, develop infrastructure, and promote innovation and digital technologies. These reforms have helped improve social conditions, strengthen national identity, and enhance Uzbekistan’s role in international relations.Overall, the article shows how the presidents of Uzbekistan— through their vision, leadership, and reforms—have contributed to building a strong, independent, and rapidly developing state that successfully combines national traditions with modern growth.